Analisis Preferensi Konsumen Beras Analog di E-Commerce - Bani, Aplonia; Tamonob, Arista Marlince; Nahak, Delila Seran (Universitas Galuh, 2025)
This study aims to provide insights for producers and stakeholders in planning the diversification of “analog rice” using “putak” flour in Kupang Regency, East Nusa Tenggara Province. Therefore, it is necessary to identify consumer preference trends and effective marketing strategies for analog rice on the “Shopee” and “Tokopedia” e-commerce platforms using the keyword “beras analog.” Qualitative data analysis was conducted using NVIVO software, while statistical analysis employed RStudio to illustrate the influence of total sales on price and rating. The results show that analog rice products are dominated by three brands—DOLLAR (corn based), SEGO (cassava-based), and FUKUMI (porang-based)—with shipping areas covering Jakarta, Madiun, and Bekasi, and peak rating distribution from 4.9 to 5. Price and rating are the primary determinants in predicting sales volume, with an increase in rating significantly boosting sales. Consumer preferences lean toward analog rice sold in bundles, with total sales exceeding 2000 compared to retail sales, indicating that higher prices do not reduce or affect total sales.